Estudo sobre o mercado livre de energia elétrica no Brasil - Cunha, Bianca Barroso Torquato [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The free energy market is an environment in which consumers can freely choose their own energy suppliers, but it is limited to large consumers. As the society becomes more interested in this kind of hiring, the government has been signaling the expansion of this market. So, the present study provides a synthesis of the restructuring that has taken place in the electrical sector in the last two decades, with focus on the development of the free energy market, presenting its structure, methodology, rules, risks, advantages and future challenges. Possible improvements are also suggested, in terms of market mechanisms, so that the expansion of the free market occurs in a sustainable manner, in order to make the Brazilian electrical sector more efficient

O mercado livre de energia elétrica é um ambiente no qual os consumidores podem escolher livremente seus próprios fornecedores de energia, porém o mesmo está limitado aos grandes consumidores. Com o aumento do interesse da sociedade sobre essa possibilidade de contratação, o governo vem sinalizando a expansão desse mercado. Nesse sentido, o estudo traz uma síntese das reestruturações que ocorreram no setor elétrico nas últimas duas décadas, com enfoque no desenvolvimento do comércio livre de energia elétrica, apresentando sua estrutura de mercado, metodologia, regras, riscos, vantagens e os desafios futuros. São sugeridos, também, possíveis aprimoramentos, em termos de mecanismos de mercado, para que a expansão do mercado livre ocorra de forma sustentável, a fim de tornar o setor elétrico brasileiro mais eficiente.
Study on the free electricity market in Brazil
Keywords: Free Energy Trade; Brazilian Electrical Sector; Free Hiring Environment; Comércio Livre de Energia; Setor Elétrico Brasileiro; Ambiente de Contratação Livre; Energia - consumo; Livre comércio; Serviço de eletricidade